DETECTION OF Giardia intestinals IN HUMAN ,CALVES AND WATER SUPPLIES BY TRADITIONAL AND MOLECULAR METHODS AT BAGHDAD CITY,IRAQ - & et al., Alhayali (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2020)
The current study was conducted during the period from July 2018 to April 2019. One hundred and forty samples from different regions of Baghdad city, Iraq, were collected from 50 calves, 40 children, and 50 water supplies for diagnosis of Giardia intestinalis. The prevalence of Giardia intestinalis in calves, children, and water by microscopic examination by using sucrose flotation, 30%, 27.5%, and 16% respectively. Twelve positive PCR products were sequenced and deposited in the Genebank database for the first time in Iraq, phylogenic analysis demonstrated that 5 sequences belong to G.intestinalis for human(MN244831, MH925331, MN244829, MN244828, MN244830), 3 sequences for calves (MN244827, MH 925332, MN244826 ), while 4 sequences for water supplies (MH886413, MN244912, MN244910, MN244911).